2013
DOI: 10.1177/0956462412473889
|View full text |Cite
|
Sign up to set email alerts
|

Liver function test abnormalities in Nigerian patients with human immunodeficiency virus and hepatitis B virus co-infection

Abstract: Data on baseline hepatic function of HIV and hepatitis B virus (HBV) co-infected patients are limited in sub-Saharan Africa. We assessed liver function test (LFT) abnormalities in Nigerian patients with HIV/HBV co-infection to highlight the impact of HIV on HBV-related liver disease in sub-Saharan Africa. A cross-sectional study involving 100 HIV/HBV co-infected patients and 100 age- and sex-matched HBV mono-infected controls. Blood testing for HIV antibodies, CD4+ cell count, hepatitis B surface antigen (HBsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…4%, P = 0.02) and FIB-4 score (13% versus. 2%, P = 0.001) among HBV coinfected HIV patients compared to HIV monoinfected participants [ 22 ]. A similar trend was observed in the index study where we found that HIV/HBV coinfected participants had eight times higher risk of liver fibrosis than the HBV monoinfected group.…”
Section: Discussionmentioning
confidence: 99%
“…4%, P = 0.02) and FIB-4 score (13% versus. 2%, P = 0.001) among HBV coinfected HIV patients compared to HIV monoinfected participants [ 22 ]. A similar trend was observed in the index study where we found that HIV/HBV coinfected participants had eight times higher risk of liver fibrosis than the HBV monoinfected group.…”
Section: Discussionmentioning
confidence: 99%
“…Liver enzymes are important biomarkers of the degree of liver damage and are easily available for the monitoring of patients with liver disease in developing countries, where the menace of this disease is high, with inadequate invasive diagnostic facilities [ 49 ]. Elevated alanine aminotransferase (ALT) levels are the most frequently used indicator for chronic liver disease.…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…According to a study in Kenya, 15 HBV/HIV coinfected women have a higher risk for abnormal ALT elevations compared to HIV-1 mono-infected women (HR 2.37; 95% CI 1.1-5.3). In Nigeria, 16 HBV/HIV coinfected patients had impaired liver function enzymes more than the controls (p=0.04). ALP was also significantly higher in the HBV/HIV coinfection group than in the HIV-1 monoinfection group.…”
mentioning
confidence: 94%